Peixes em áreas rasas do estuário do rio São Mateus, Espírito Santo - Bolzan, Michelle Sequine (2014)
The estuaries are coastal semi-enclosed environments and within sea water is measurably diluted with freshwater derived from land drainage and mainly influenced by tides, winds and continental runoff. Estuaries are still considered highly productivity and shelters heterogeneous habitats such as mangrove forests, tidal creeks, tidal mud flats and sandy beaches. The present study aims to describe the spatial and temporal variation of fish assemblage structure and composition of shallow habitats of São Mateus river estuary, Espírito Santo. For this, monthly samples from July/2012 to June/2013 were carried out in 8 shallow areas of the São Mateus river estuary. For each site was performed three replicates using seine net for fish samples concomitantly to water abiotic measures (temperature, salinity, turbidity and depth). Significantly differences of abiotic variables were verified among seasons and sites. Fish assemblage comprised mainly juvenile and small-sized fish. Fish composition, biomass, density and number of species differed significantly among seasons and sites. Small recruits of Atherinella brasiliensis and Ctenogobius boleosoma were most abundant in autumn, while Rhinosardinia bahiensis and Centropomus undecimalis showed high abundances during the winter season. Regarding spatial fish distribution, R. bahiensis, Trinectes paulistanus, C. undecimalis and C. parallelus were most abundant in sites of the upper estuary area, whereas Sphoeroides testudineus and C. boleosoma were abundant in the middle estuary area and A. brasiliensis in sites of the lower estuary area. Water salinity was most important variable for A. brasiliensis and S. spengleri distribution, whereas Anchovia clupeoides, C. undecimalis, C. parallelus and Gobionellus oceanicus were positive correlated with water depth. The fish species T. paulistanus, Genidens genidens and Achirus lineatus were related with water turbidity. Thus, the shallow waters habitats of São Mateus river